(untitled) (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2018)
Leihitu is the name of a district that has several villages known as the Leihitu peninsula, located in the northern part of the island of Ambon. In the history of the peninsula is also called the term "Land Hitu". Besides that, a new position which was characterized by Islam and dominated the government began to emerge, such as; Maulana, Imam, Qadhi, Hukom, Khatib and Modim. Interesting research is how the philosophy of the name of the Peninsula for the kingdom of Leihi, whether the name of the Peninsula has an influence on the formation of "lands" in the peninsula, especially in the Land of Hitu in the 16th and 17th centuries. Is there a hierarchical relationship with the Arabian Peninsula at the beginning of the development of Islamic da’wah in the kingdom to influence the religious education of the Leihitu? Through the phenomenological research methods of phenomenology, history and anthropology of religion, it is possible to explore data and data analysis in depth, especially in terms of the philosophy of the meaning contained in the name of the kingdom of the Leihitu Peninsula whose communities are phenomenally the majority embracing Islam even though it coexists with Christianity. The aim is to find out the meaning of the name of the Jazirah attached to a village or village which is quite far from the center of Ambon city, which also contains special meaning as it is specific to the naming of the Arabian Peninsula where the Prophets and Apostles appear.